Studying Science Inequities: How to Use Surveys to Study Diverse Populations. Issue 1 (March 2022) - Bayes, Robin; Druckman, James N.; Safarpour, Alauna C.
Scholars have long documented unequal access to the benefits of science among different groups in the United States. Particular populations, such as low-income, non–white people, and Indigenous people, fare worse when it comes to health care, infectious diseases, climate change, and access to technology. These types of inequities can be partially addressed with targeted interventions aimed at facilitating access to scientific information. Doing so requires knowledge about what different groups think when it comes to relevant scientific topics. Yet data collection efforts for the study of most science-based issues do not include enough respondents from these populations. We discuss this gap and offer an overview of pertinent sampling and administrative considerations in studying underserved populations. A sustained effort to study diverse populations, including through community partnerships, can help to address extant inequities.